Ultrasound-assisted modified paramedian approach vs. traditional paramedian approach for spinal anesthesia in lower limb surgery: a single-center randomized controlled trial - Wudong Zhuang; Xiaoyuan Li; Jianhua Wang; Ruizhao Lyu; Shan Wang; Rui Liu; Yang Bai (Frontiers in Medicine, 2026)
Study objective This randomized controlled trial aimed to determine whether an ultrasound-assisted modified paramedian approach could improve procedural outcomes compared with an ultrasound-assisted traditional paramedian approach for spinal anesthesia in patients undergoing lower limb surgery. Design Prospective, randomized, controlled clinical trial. Setting Operating rooms of Hebei Cangzhou Hospital of Integrated Traditional Chinese Medicine and Western Medicine, China. Patients A total of 116 patients aged 18–90 years, with a body mass index of 18–30 kg/m 2 and ASA physical status I–III, scheduled for lower limb surgery requiring spinal anesthesia were enrolled. Patients with contraindications to spinal anesthesia, previous lumbar surgery, scoliosis, or pregnancy were excluded. Interventions Patients were randomly assigned in a 1:1 ratio using a computer-generated random allocation sequence with concealed allocation to receive either ultrasound-assisted traditional paramedian spinal anesthesia (Group C, n = 58) or ultrasound-assisted modified paramedian spinal anesthesia (Group M, n = 58). Main results Compared with Group C, Group M required fewer needle passes to achieve successful cerebrospinal fluid (CSF) flow [median [IQR]: 1 [1–2] vs. 2 [1–3], P = 0.006] and demonstrated a higher first-pass success rate [37/58 [63.79%] vs. 25/58 [43.10%], P = 0.026]. Group M also showed a shorter duration of the spinal procedure [12.5 [9.0–20.0] s vs. 15.0 [10.0–32.25] s, P = 0.028] and shorter total procedure time [76.5 [65.0–89.25] s vs. 82.0 [72.0–112.75] s, P = 0.031]. The distribution of patient satisfaction scores differed between groups, with a higher proportion of patients reporting being “very satisfied” in Group M (87.93% vs. 70.69%, P = 0.040). The incidence of procedure-related and postoperative adverse events was comparable between groups, and no serious complications occurred. Conclusions The ultrasound-assisted modified paramedian approach was associated with fewer needle passes, improved first-pass success, and higher patient satisfaction ratings compared with the traditional paramedian approach, while without increasing short-term procedure-related adverse events. Further multicenter studies are warranted to determine whether these findings can be generalized to broader patient populations. Clinical Trial Registration: https://www.chictr.org.cn/showproj.html?proj=203874 , identifier ChiCTR2300075567.